Isolation and anti-neuroinflammation activity of sesquiterpenoids from Artemisia argyi: computational simulation and experimental verification - Caiwenjie La; Menghe Li; Zexu Wang; Tao Liu; Qiongzhen Zeng; Pinghua Sun; Zhe Ren; Cuifang Ye; Qiuying Liu; Yifei Wang (BMC, 2024)
Abstract Background Artemisia argyi is a traditional herbal medicine belonging to the genus Artemisia that plays an important role in suppressing inflammation. However, the chemical constituents and underlying mechanisms of its therapeutic potential in neuroinflammation are still incompletely understood, and warrant further investigation. Methods Several column chromatography were employed to isolate and purify chemical constituents from Artemisia argyi, and modern spectroscopy techniques were used to elucidate their chemical structures. The screening of monomeric compounds with nitric oxide inhibition led to the identification of the most effective bioactive compound, which was subsequently confirmed for its anti-inflammatory capability through qRT‒PCR. Predictions of compound-target interactions were made using the PharmMapper webserver and the TargetNet database, and an integrative protein-protein interaction network was constructed by intersecting the predicted targets with neuroinflammation-related targets. Topological analysis was performed to identify core targets, and molecular docking and molecular dynamics simulations were utilized to validate the findings. The result of the molecular simulations was experimentally validated through drug affinity responsive target stability (DARTS) and Western blot experiments. Results Seventeen sesquiterpenoids, including fifteen known sesquiterpenoids and two newly discovered guaiane-type sesquiterpenoids (argyinolide S and argyinolide T) were isolated from Artemisia argyi. Bioactivity screening revealed that argyinolide S (AS) possessed the most potent anti-inflammatory activity. However, argyinolide T (AT) showed weak anti-inflammatory activity, so AS was the target compound for further study. AS may regulate neuroinflammation through its modulation of eleven core targets: protein kinase B 1 (AKT1), epidermal growth factor receptor (EGFR), proto-oncogene tyrosine-protein Kinase (FYN), Janus Kinase (JAK) 1, mitogen-activated protein (MAP) Kinase 1,8 and 14, matrix metalloproteinase 9 (MMP9), ras-related C3 botulinum toxin substrate 1 (RAC1), nuclear factor kappa-B p65 (RELA), and retinoid X receptor alpha (RXRA). Molecular dynamics simulations and DARTS experiments confirmed the stable binding of AS to JAK1, and Western blot experiments demonstrated the ability of AS to inhibit the phosphorylation of downstream Signal transducer and activator of transcription 3 (STAT3) mediated by JAK1. Conclusions The sesquiterpenoid compounds isolated from Artemisia argyi, exhibit significant inhibitory effects on inflammation in C57BL/6 murine microglia cells (BV-2). Among these compounds, AS, a newly discovered guaiane-type sesquiterpenoid in Artemisia argyi, has been demonstrated to effectively inhibit the occurrence of neuroinflammation by targeting JAK1.